Letter - Tewson, Vincent
1940-04-06 038-0044-001 HVT/FC/EK/835 April 6. 1940 TELEPHONE DUNKELD 34. EASTWOOD, DUNKELD, PERTHSHIRE. Dear Mr. Tewson, Many thanks for writing so fully. Of course I understand what a drain on your funds must have been caused by the Spanish seamen - Could none of them be emigrated to S. America, or could they not get jobs in our mercantile marine? However, they are your affair, not mine! Yes, I know that the sum you mentioned was to be largely for dilapidations & 'winding up', but we have reached the day of several dilapidations, which are greatly adding to our difficulties. If any help could be given us with these 292/946/38/44(I)